2007
DOI: 10.1038/sj.ejcn.1602959
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and non-genetic correlates of vitamins K and D

Abstract: Objective: To assess the genetic and nongenetic correlates of circulating measures of vitamins K and D status in a communitybased sample of men and women. Subjects/Methods: A cross-sectional study of 1762 participants of the Framingham Offspring Study (919 women; mean age 59 years). Vitamin K status was measured as plasma phylloquinone and serum percent undercarboxylated osteocalcin (ucOC), and vitamin D was measured using plasma 25-hydroxyvitamin D (25(OH)D). Associations between vitamin K status and vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(161 citation statements)
references
References 38 publications
5
151
2
3
Order By: Relevance
“…Whereas no significant heritability was reported in 2 biomarkers of vitamin K status in a crosssectional study of almost 2000 subjects, 33 the minor allele G of the identical SNP was associated with higher concentrations 22 Taken together, at the present time, there are insufficient data to support the contention that factors that influence VKORC1 activity potentially modify arterial disease via its chronic impact on peripheral vitamin K status.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Whereas no significant heritability was reported in 2 biomarkers of vitamin K status in a crosssectional study of almost 2000 subjects, 33 the minor allele G of the identical SNP was associated with higher concentrations 22 Taken together, at the present time, there are insufficient data to support the contention that factors that influence VKORC1 activity potentially modify arterial disease via its chronic impact on peripheral vitamin K status.…”
Section: Discussioncontrasting
confidence: 40%
“…Whereas no significant heritability was reported in 2 biomarkers of vitamin K status in a crosssectional study of almost 2000 subjects, 33 the minor allele G of the identical SNP was associated with higher concentrations …”
Section: Discussionmentioning
confidence: 99%
“…Results of twin studies have suggested a heritable component of circulating 25-OH-vitamin D concentrations, with heritability rates ranging from 29% to 77% (12,13,14 ). Genomewide association studies identified 3 common loci of genetic determinants for vitamin D insufficiency: group-specific component (GC, rs2282679), 9 7-dehydrocholesterol reductase (DHCR7, rs12785878), and cytochrome P450 IIR-1 (CYP2R1, rs10741657).…”
Section: -Hydroxy-vitamin D (25-oh-vitamin D)mentioning
confidence: 99%
“…Д ля оптимального течения биохимических процессов плоду и новорожденному необ-ходимо адекватное поступление витаминов [1]. Исследования в условиях Европейского Севера не-многочисленны: выявлены особенности обмена витамина С у новорожденных [2], проведено иссле-дование обеспеченности диады мать-ребенок жи-рорастворимыми витаминами А, Е и водораствори-мыми витаминами В 1 , В 2 [3], отмечены особенности метаболического и микронутриентного статуса но-ворожденных детей [4].…”
unclassified